Acute liver failure due to Human Herpesvirus 6 in an infant (La Pediatria Medica e Chirurgica, 2012)
We report a case of a 4-months infant with fever in the absence of other specific symptoms that has rapidly and unexpectedly developed acute liver failure (ALF) with coagulopathy and complicated with bone marrow failure without encephalopathy. The main viral infection agents (hepatitis virus A, B, C, Citomegalovirus, Ebstain Barr virus, Parvovirus B19, Adenovirus), drug-induced hepatotoxicity and metabolic disorders associated to ALF were excluded. Quantitative determination of Human Herpesvirus 6 (HHV6) genome was positive with a significant number of copies for mL. A favorable evolution of the clinical symptoms and a progressive hematochemical resolution were obtained. Plasma and Vitamin K were administrated as a support therapy for treating coagulopathy. The present case report and the cases’ review from the literature, evidence the importance of always including screening for HHV6 infection in the diagnostic approach to acute onset of liver failure. HHV6 is a common virus in the pediatric population with a greater number of cases of fulminant viral non-A, non-B, non-C hepatitis in immunocompetent patients due to this virus: these forms have often a high mortality rate and maybe necessitate liver transplantation; for this reason correct etiological agent identification is mandatory for the prognosis and it has to be based on the quantitative search of the virus’s genome. Pathogenesis of liver-induced damage associated to HHV6 remains unclear; however in vitro studies demonstrate the potential hepatotoxicity effects of this virus.
Keywords: Human Herpesvirus 6; acute liver failure; hypertransaminasemia